HAD hydrolase function unveiled by substrate screening: Enzymatic characterization of Arabidopsis thaliana subclass I phosphosugar phosphatase AtSgpp - Caparrós-Martín, Jose; McCarthy-Suárez, I.; Culiáñez-Macià, F. (Springer, 2013)
This work presents the isolation and the biochemical characterization of the Arabidopsis thaliana gene AtSgpp. This gene shows homology with the Arabidopsis low molecular weight phosphatases AtGpp1 and AtGpp2 and the yeast counterpart GPP1 and GPP2, which have a high specificity for dl-glycerol-3-phosphate. In addition, it exhibits homology with DOG1 and DOG2 that dephosphorylate 2-deoxy-d-glucose-6-phosphate. Using a comparative genomic approach, we identified the AtSgpp gene as a conceptual translated haloacid dehalogenase-like hydrolase HAD protein. AtSgpp (locus tag At2g38740), encodes a protein with a predicted Mw of 26. 7 kDa and a pI of 4. 6. Its sequence motifs and expected structure revealed that AtSgpp belongs to the HAD hydrolases subfamily I, with the C1-type cap domain. In the presence of Mg 2+ ions, the enzyme has a phosphatase activity over a wide range of phosphosugars substrates (pH optima at 7. 0 and K m in the range of 3. 6-7. 7 mM). AtSgpp promiscuity is preferentially detectable on d-ribose-5-phosphate, 2-deoxy-d-ribose-5-phosphate, 2-deoxy-d-glucose-6-phosphate, d-mannose-6-phosphate, d-fructose-1-phosphate, d-glucose-6-phosphate, dl-glycerol-3-phosphate, and d-fructose-6-phosphate, as substrates. AtSgpp is ubiquitously expressed throughout development in most plant organs, mainly in sepal and guard cell. Interestingly, expression is affected by abiotic and biotic stresses, being the greatest under Pi starvation and cyclopentenone oxylipins induction. Based on both, substrate lax specificity and gene expression, the physiological function of AtSgpp in housekeeping detoxification, modulation of sugar-phosphate balance and Pi homeostasis, is provisionally assigned. © 2012 The Author(s).